Uma sequência didática para o ensino do modelo padrão - Bastos, Kleber da Luz (2023)
Teaching Physics is a challenge faced by many teachers at various levels of education and modalities. The nature of the challenge has two elements that have been discussed by several researchers who study the teaching of physics: (1) the complexity of the theories of physics and (2) the process of teaching and learning knowledge of physics. This scenario seems to intensify when we deal with concepts from the field of Modern and Contemporary Physics, in which Quantum Mechanics, Relativistic Mechanics and Quantum Field Theory dictate the discussions about matter, its constituents and the interactions involved. From this fantastic universe of theories, laws and concepts arising from a process of (human) construction of knowledge arises the Standard Model. This model organizes elementary particles according to their properties in the form of a table, which by many is considered the Periodic Table of Physics. To contribute with innovative actions so that students can have a better understanding of the structure of the matter, this research proposed to investigate how the teaching of the Standard Model can contribute to this learning, following the cognitivist theory of Meaningful Learning as a methodology. Using qualitative research as a structure and epistemological foundation of action research of the strategic type within a cyclical process, 5 teaching units were idealized following active methodologies, with implementation through a didactic sequence, being the basis of the educational product. As data collection instruments, the use of questionnaires and the systematization of learning after the script of practical activities were followed by the observation of the intended results, according to the verification of performance by the rubric. It is then stated that according to the results of the research, the material used connected with the cognitive structure of the learner in a relevant way, and that the learner in a non-arbitrary and non-literal way related his anchor ideas with the learning activities, indicating indications of more significant learning. As results we point out that the identification of concepts is necessary for the knowledge of the MP, the organization and planning of teaching and learning actions, the use of technological resources with experiments that show the way of investigating the structure of the matter and the games in teaching, are facilitators of the process.